2008
DOI: 10.1111/j.1751-0813.2008.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelled female sale options demonstrate improved profitability in northern beef herds

Abstract: Generalised recommendations on improving reproductive performance are not necessarily the most cost-effective strategy to improve breeder herd profitability. Judicious use of simulation models is essential to help develop the best turnoff strategies for females and to improve station profitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…In addition, the live export trade with south‐east Asia has a strict requirement of non‐pregnant females. It has been recently demonstrated that there can be significant economic returns to cattle producers from spaying surplus females 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the live export trade with south‐east Asia has a strict requirement of non‐pregnant females. It has been recently demonstrated that there can be significant economic returns to cattle producers from spaying surplus females 2 …”
mentioning
confidence: 99%
“…It has been recently demonstrated that there can be significant economic returns to cattle producers from spaying surplus females. 2 Currently in northern Australia, because of the difficulty in controlling bulls and with many herds being continuously mated, the only method of reliably and permanently preventing pregnancy is surgical spaying. Until the mid-1990s the most common method of spaying cattle in northern Australia was via a flank incision through the abdominal wall.…”
mentioning
confidence: 99%
“…Management and marketing options for large and extensively managed beef cattle stations in northern Australia are very different from those in the south in terms of season, nutrition, geography, management and genetic factors, including the increased numbers of Bos indicus cattle. This study examined the impact of a variety of management factors on the profitability of breeding properties using modelling with Bcowplus software 1 . Breeder herd performances and production parameters including prices, costs and herd structure, were collected from properties in six beef‐producing regions in northern Australia, all of which spay females to enhance their marketing options.…”
Section: Production Animalsmentioning
confidence: 99%
“…The sale of surplus to requirement cows, "culled cows", is an important contributor to the overall profit of northern Australia beef breeding businesses, with the sale of cull cows contributing up to 50% of the total income (Niethe & Holmes 2008). In northern Australian beef enterprises, cows are typically culled from the herd for two reasons: unproductive and culled for age.…”
Section: Introductionmentioning
confidence: 99%
“…However, cull cows often present at muster in poor body condition (i.e. low body weight, body condition score, and carcass quality) and are difficult to market for slaughter (Roeber et al 2001;Niethe & Holmes 2008). The value of cull cows is improved by realimenting cows through feed supplementation and intensive feeding to meet higher market values (Holmer et al 2009;Moreno et al 2012).…”
Section: Introductionmentioning
confidence: 99%